The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1152/jn.00803.2016
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide promotes GABA release by activating a voltage-independent Ca2+ influx pathway in retinal amacrine cells

Abstract: Retinal amacrine cells express nitric oxide (NO) synthase and produce NO, making NO available to regulate the function of amacrine cells. Here we test the hypothesis that NO can alter the GABAergic synaptic output of amacrine cells. We investigate this using whole cell voltage clamp recordings and Ca imaging of cultured chick retinal amacrine cells. When recording from amacrine cells receiving synaptic input from other amacrine cells, we find that NO increases GABAergic spontaneous postsynaptic current (sPSC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…In chick ACs in vitro, NO transiently reverses GABA-and glycine-gated currents, converting inhibition of ACs into excitation, thereby increasing the firing of these cells and thus enhanced inhibitory drive on their synaptic partners (e.g., RGCs). This NO-induced shift in E Cl− is likely due to release of Cl − from intracellular stores (Hoffpauir et al, 2006;Krishnan and Gleason, 2015;Krishnan et al, 2017;Maddox and Gleason, 2017;Maddox et al, 2018). In addition, NO may drive synaptic glutamate release from BCs without membrane depolarization via a TRPC Ca 2+ influx-mediated pathway, as shown in the chick retina (Maddox et al, 2018), further depolarizing ACs.…”
Section: Why Do Amacrine Cells Become Hyperactive? a Hypothesismentioning
confidence: 90%
“…In chick ACs in vitro, NO transiently reverses GABA-and glycine-gated currents, converting inhibition of ACs into excitation, thereby increasing the firing of these cells and thus enhanced inhibitory drive on their synaptic partners (e.g., RGCs). This NO-induced shift in E Cl− is likely due to release of Cl − from intracellular stores (Hoffpauir et al, 2006;Krishnan and Gleason, 2015;Krishnan et al, 2017;Maddox and Gleason, 2017;Maddox et al, 2018). In addition, NO may drive synaptic glutamate release from BCs without membrane depolarization via a TRPC Ca 2+ influx-mediated pathway, as shown in the chick retina (Maddox et al, 2018), further depolarizing ACs.…”
Section: Why Do Amacrine Cells Become Hyperactive? a Hypothesismentioning
confidence: 90%
“…The involvement of SVs in the NOdrCl is especially relevant to AC function because ACs participate in serial [ 74 ] and reciprocal synapses [ 21 ] such that presynaptic Cl - can affect the sign of nearby incoming GABAergic synapses in a highly localized fashion [ 22 24 ]. We have also recently demonstrated that the NO donor SNAP can increase spontaneous and evoked GABA release via presynaptic activation of TRPC5 channels [ 41 , 75 ] providing an additional NO-dependent mechanism for enhancing GABAergic output from ACs.…”
Section: Discussionmentioning
confidence: 99%
“…For autaptic recordings, the ACs were not in contact with other neurons, ruling out synaptic input from unclamped cells. Charge transfer at autapses was calculated as previously described and reported as pC [ 41 ]. Inward Ca 2+ currents were often contaminated and obscured by outward synaptic current during the voltage step.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, two reports on the role of CFTR in neuronal cytosolic Cl Ϫ homeostasis demonstrate effects of CFTR inhibitors on cytosolic Cl Ϫ in the absence of stimulated PKA activity (Morales et al 2011;Ostroumov et al 2011), implying significant baseline CFTR (and possibly PKA) activity in those neurons. A third possibility is that the Ca 2ϩ elevations that we know are generated by NO in amacrine cells (Maddox and Gleason 2017) activate the Ca 2ϩ -sensitive adenylate cyclase, adenylate cyclase 1. CFTR activation via adenylate cyclase 1 has been previously demonstrated (Billet and Hanrahan 2013).…”
Section: Discussionmentioning
confidence: 99%